2016
DOI: 10.1088/1054-660x/26/10/105105
|View full text |Cite
|
Sign up to set email alerts
|

A multi-wavelength erbium-doped fiber ring laser using an intrinsic Fabry–Perot interferometer

Abstract: In this experimental paper, a multi-wavelength erbium-doped ring fiber laser based on an all fiber intrinsic Fabry–Perot interferometer is presented and demonstrated. The interferometer was fabricated by an arc and splicing technique using hollow core photonic crystal fiber (HCPCF) and conventional single mode fiber (SMF28). The fiber laser can be operated in single, dual and triple lasing mode by applying a transversal load over the all fiber interferometer. The laser spectrums present minimal mode spacing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, the fiber laser arrangement can be used for remote sensing applications. Despite the power instabilities observed, the laser offers better performance than some works [14,18]. The laser presented in this work is an alternative, cost-effective setup for tuning multi-wavelength spectra using simple and easy-to-control techniques.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the fiber laser arrangement can be used for remote sensing applications. Despite the power instabilities observed, the laser offers better performance than some works [14,18]. The laser presented in this work is an alternative, cost-effective setup for tuning multi-wavelength spectra using simple and easy-to-control techniques.…”
Section: Discussionmentioning
confidence: 94%
“…For several decades, the ability to generate tunable or switched multi-wavelength fiber lasers has been one of the focuses pursued by the fiber laser community. These lasers are associated with many reliable applications related to multi-wavelength spectra such as optical fiber sensors [1][2][3][4][5][6][7][8][9], spectroscopy systems [10], biomedical imaging [11], telecommunications [12], microwave photonics [13], and radio frequency optical domain systems [14]. These applications require achieving compact configuration, stable emission, narrow linewidth, and adequate spacing mode.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various approaches have been reported to achieve multi-wavelength oscillation in EDF lasers. Most of these ring fiber laser cavities are based on all-fiber structures such as arrayed waveguide gratings [7], fiber Bragg gratings (FBGs) [8][9][10], Mach-Zehnder interferometers (MZI) [11,12], Fabry-Perot interferometers [13,14], nonlinear fibers [15], tapered fibers [16] and Sagnac interferometers [17,18]. Yeh et al demonstrated a stabilized single-longitudinal-mode (SLM) dual-wavelength EDF laser triple-ring cavity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Till now, many different kinds of filters have been designed for multi-wavelength laser generation, such as Fabry-Perot filter [9]- [11], Mach-Zehnder interferometer [12]- [14], Bragg gratings [15], [16], Spatial mode beating filter [17], [18], Sagnac loop filter [19], and Lyot birefringent filter [20]. Meanwhile, to obtain the stable multi-wavelength laser operation at room temperature, various approaches, including polarization hole burning [21], [22], four-wave mixing [23]- [25], stimulated Brillouin scattering [26], [27], nonlinear optical loop mirror (NOLM) [28]- [30], and nonlinear amplifier loop mirror (NALM) [31] have been proposed and demonstrated to alleviate the strong mode competition caused by homogeneous gain broadening in rare-earth ions doped fiber.…”
Section: Introductionmentioning
confidence: 99%